The role of primary transoral laser microsurgery in laryngeal cancer: a retrospective study. (October 2015) - To, K.; Qureishi, A.; Mortimore, S.; De, M.
<x xml:space="preserve">Abstract</x> Objective To investigate the oncologic and survival outcomes of primary transoral laser microsurgery in laryngeal cancer. Design Retrospective analysis of a database of all patients undergoing primary transoral laser microsurgery with or without adjunctive therapy from June 2000 to October 2013. The median follow‐up time was 33 months. Setting A teaching hospital. Participants Two hundred and three patients underwent primary transoral laser microsurgery. Of these, 166 had glottic and 37 had supraglottic squamous cell carcinoma. Main outcome measures Overall survival, disease‐specific survival, local control and rate of salvage laryngectomy. Results Primary transoral laser microsurgery was performed exclusively in 149 (73%) patients, 16 (8%) had transoral laser microsurgery followed by postoperative (chemo)radiotherapy, 6 (3%) had transoral laser microsurgery with neck dissection, and 32 (16%) had transoral laser microsurgery in combination with neck dissection and postoperative (chemo)radiotherapy. In glottic cancer, the 5‐year local control was 86%, 86% and 76% in carcinoma in situ (Tis), early‐stage (T1, T2) and late‐stage (T3, T4) disease, respectively. The 5‐year disease‐specific survival was 93% in Tis, 96% in early‐stage and 65% at late‐stage disease. In supraglottic cancer, the 5‐year local control was 66% in early‐stage and 88% in late‐stage disease. The 5‐year disease‐specific survival was 80% and 75%, respectively. The rate of salvage laryngectomy was 9.9%. Conclusion In carefully selected patients with laryngeal cancer, primary transoral laser microsurgery with or without adjunctive therapy can be organ preserving. It can provide a valid treatment option for patients.